Pelarsen Windows : humans v. robots - Ansari, Shahid, (SAGE Knowledge. Cases., 2008)
Pelarsen produces a variety of wood windows ranging from simple standard to very complex architectural windows produced at the company's old and new plants. The older plants are traditional mass production plants that are labor intensive, have large inventories, and have a lot of spoilage. The newer plants use computer integrated robotics equipment, run a lean operation with small inventories, and have few quality issues. Doug Niedermeyer, manager of an older plant, is complaining that his plant's poor profitability is caused by the lack of new robotics equipment and wants more high margin architectural window business. His claim is supported by plant profit projections based on the cost data from his plant's volume-based accounting system. However, a deeper analysis of his plant's production processes, capacity utilization, quality capability, inventory levels, and spoilage rates suggests that he can take many short-term actions to increase profits and that his real profitability problem may lie in the mismatch among his production processes, product mix, and cost structure.